A study of students’ language strategies use and difficulties during group discussions - Anis, Maesin; Surina, Nayan; Nazira, Osman; Mahani, Mansor; Latisha Asmaak, Shafie (Universiti Malaysia Perlis (UniMAP), 2011)
The 2nd International Conference on the Roles of Humanities and Social Science in Engineering (ICoHSE 2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 14th November 2010 at Bayview Beach Resort, Penang, Malaysia.